2013
DOI: 10.1590/s1413-35552012005000095
|View full text |Cite
|
Sign up to set email alerts
|

30o inclination in handles of plastic boxes can reduce postural and muscular workload during handling

Abstract: | Background: The handling of materials, which occurs in the industrial sector, is associated with lesions on the lumbar spine and in the upper limbs. Inserting handles in industrial boxes is a way to reduce work-related risks. Although the position and angle of the handles are significant factors in comfort and safety during handling, these factors have rarely been studied objectively. Objective: To compare the handling of a commercial box and prototypes with handles and to evaluate the effects on upper limb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
2
0
1
Order By: Relevance
“…Con respecto a las medidas de control y prevención sugeridas por la GATISO de dolor lumbar inespecífico, la disminución del peso de la carga, 13 el diseño de puntos de agarre de la carga y las ayudas mecánicas para la manipulación, 34,36,37,39,40 fueron los únicos que coincidieron con la presente investigación, los dispositivos de adaptación al cuerpo, la medidas administrativa del levantamiento de cargas divididas y la implementación del peso máximo aceptable para los trabajadores fueron nuevos aportes.…”
Section: Discussionunclassified
“…Con respecto a las medidas de control y prevención sugeridas por la GATISO de dolor lumbar inespecífico, la disminución del peso de la carga, 13 el diseño de puntos de agarre de la carga y las ayudas mecánicas para la manipulación, 34,36,37,39,40 fueron los únicos que coincidieron con la presente investigación, los dispositivos de adaptación al cuerpo, la medidas administrativa del levantamiento de cargas divididas y la implementación del peso máximo aceptable para los trabajadores fueron nuevos aportes.…”
Section: Discussionunclassified
“…On the other hand, Shih and Wang [24] recommended inclinations between -10° and 10° to allow neutral wrist posture (0° of deviation) for both genders evaluated. The most recently published paper from Silva et al [25] observed that 30° inclination in handles enabled safer scores on all variables tested at different heights of handling. With better methodological quality, Silva et al [25] used different measurement methods that were complementary in evaluating the upper limbs during handling with different grip designs.…”
Section: Discussionmentioning
confidence: 99%
“…This handle positioning was associated with the reduction of spinal load due to smaller ranges of flexion, corresponding to a reduction of 4.5 kg of load on the lumbar region. On the other hand, more recent studies [11, 14, 25, 30], which evaluated load on upper limbs, suggested that handle modifications should be made according to the handling height. Handles located at the upper part of the box may create higher demands on upper limbs when the load is placed in higher places.…”
Section: Discussionmentioning
confidence: 99%